Estimating and comparing the concentration of some heavy metals in local and imported red pepper powder available in the markets of Bani Walid - ام السعد فرج عمر (African Journal of Advanced Pure and Applied Sciences, 2025)
The moisture, ash, and fiber content were studied using analytical methods approved by the Association of Official Analytical Chemists (AOAC, 1992), in addition to the concentrations of one element (cadmium, lead, and copper) in three types of red pepper (local, Indian, Spanish). The samples were obtained from local markets and mills in the city of Bani Walid and were randomly selected due to their abundance. The results showed that Indian red pepper has the highest ash content (10.96%) and the highest copper concentration (0.178 mg/kg) with the lowest moisture content (6.26%). This reflects the effect of drying processes in increasing mineral content. Meanwhile, Spanish peppers were characterized by the highest fiber content (36.5%), indicating a denser cellular structure and higher fiber content. As for Libyan pepper, it showed a remarkable chemical balance between the percentage of ash (8.86%), moisture (11.69%), and fiber (35%), along with moderate levels of mineral elements. This makes it an average model in terms of quality and food safety. The very low values of heavy metals, Cadmium <0.001, Lead ≤0.186 (mg/kg), confirm the safety of the samples and their freedom from contaminants within the limits recommended by the World Health Organization (WHO) and the Food and Agriculture Organization (FAO), making the three types of red pepper safe for human consumption.